Optimization of a multi-residue method for 101 pesticides in green tea leaves using gas chromatography–tandem mass spectrometry - Hou,Xue (2016)
ABSTRACT A method for analysis of 101 pesticide residues in tea leaves was developed and validated for the first time. Pure acetonitrile was used as extraction solvent rather than acetonitrile after matrix hydration based on the amount of co-extracts and recoveries performance. During clean-up procedure, primary-secondary amine/graphitized carbon black (500 mg) was selected, which exhibited outstanding properties in clean-up capabilities and recoveries of pesticides comparing to primary-secondary amine/graphitized carbon black (250 mg), NH2-Carbon and TPT absorbents. The method was validated employing gas chromatography coupled to tandem mass spectrometry at the spiked concentration levels of 0.050 and 0.100 mg kg−1. For most of the targeted pesticides, the percent recoveries range from 70 to 120%, with relative standard deviations <20%. The linear correlation coefficients (r 2) were higher than 0.99 at concentration levels of 0.025–0.250 mg kg−1. Limits of quantification ranged from 1.1 to 25.3 µg kg−1 for all pesticides. The developed method was successfully applied to the determination of pesticides in tea leaf samples.